Use of Puffery in Advertisements and its Effect on Consumer Attitude: An Empirical Study in Pune City - Dr. Surbhi Jain, Shivani Dorge (International Journal of Advanced Science and Technology, 2020)
Advertisements today have developed to be an essential part of the socio-economic system ofsociety. Puffery is an advertising type which praises the product that needs to be advertisedby means of opinions that are rather subjective, overemphasizedand mostly, affirming no particular facts. Advertisements every so often possess puffery withmetaphorsthat appear to be significant but in realityoffervery little information. Consumers’ responses to these metaphorsrely on the way they perceive themselves to be relatively knowledgeable about the item than others whom the advertisements is explicitlyexpected to encourage. When an advertisementis shown in a professional weekly or monthlywhich is mostlyread by experts in the product area, puffery in generalintensifies the effectiveness of the advertisements. When readers consider they know as much as or more than over-all consumers, puffery cutsdown the effectiveness of the advertisements. Furthermore, the media setting through which an advertisement is shown has a direct effect on decisionstaken by consumers who recognizethemselves to have much lesser knowledge regarding the product or an item that is promoted. This paper demonstratesin what way puffery advertisement affects the attitude of consumers towards a product and by what means the firms are using their skillsand methods for increasing the pressure on consumers to buy a product that is being promoted.